High-dose interferon results in high HBsAg seroclearance in children with chronic hepatitis B infection - (:unkn) unknown (TURKISH J PEDIATRICS, 2003)
Clinical trials for chronic hepatitis B (HBV) infection in children have shown usefulness of interferon alpha 2b (IFN-alpha) in eliminating HBV replication and in improving liver histology. Although it is not-the ultimate goal of the interferon treatment for chronic HBV infection, it has been suggested in adults that HBsAg clearance decreases the likelihood of development of hepatocellular carcinoma, and prolongs, the survival. HBV DNA clearance has been shown to be higher with higher doses of interferon in children, but it was rarely associated with HbsAg clearance. Ten MU/m(2) was tried in 46 children who had biopsy-proven chronic HBV infection. They received IFN-a subcutaneously three times/week for six months. The treatment regimen was completed in 41 children and the second liver hiopsy was carried out one year after the end of the treatment in 30 of 41 patients, With this schedule, 15 (36.6%) children showed persistent loss of HBV DNA 12 months after the cessation of the treatment, 20 (48.7%) lost HBeAg, and eight (19.5%) developed anti-HBs antibody with loss of HBsAg. A significant improvement in liver histology was obtained in children with HBV DNA clearance. Serum ALT levels normalized in. all HBeAg seroconverters. These findings suggested that. the 10 MU/m(2) IFN-a treatment was well tolerated and resulted in, a high rate of HbsAg clearance in addition to HBV. DNA clearance in a roup. of chidren with chronic HBV infection.
Keywords: hepatitis B virus; high-dose interferon; children; ALPHA-INTERFERON; CONTROLLED-TRIAL; FOLLOW-UP; THERAPY; CLEARANCE